People Living with HIV/AIDS (PLWHA) based on clinical characteristics - Yudhi Atmajaya; Suharmanto Suharmanto; Jhons Fatriyadi Suwandi; Susianti Susianti (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background : Since it was discovered and identified ten years ago, the Human Immunodeficiency Virus (HIV) has the potential to produce the immunodeficiency syndrome condition known as Acquired Immunodeficiency Syndrome (AIDS). In the 2020-2024 National Medium-Term Development Plan (RPJMN), one of the policy and strategy directions is to increase access and quality of health services towards universal health coverage. Improving disease control, where HIV AIDS and sexually transmitted infections are part of the policy direction. In order to improve the quality of services for PLWHIV, it is necessary to have a comprehensive perspective of the medical officers, so there is a need for patient mapping based on the characteristics of the patients being treated.Purpose: To determine the description of the clinical stage based on characteristics of PLWHIV at the Sukabumi Public Health Center, Bandar Lampung in 2021.Method: This study is a quantitative descriptive observational study with a cross-sectional approach.Results : The results of the study, it is known that the characteristics of PLWHIV based on gender that's male are 67%, there 41.7% of PLWHIV are 31-40 years old, level of education PLWHIV are 67% have a senior high school, 52.4% as private employees, and 62,1% of PLWHIV live in cities. The results showed that at stage 1 the age group was 21-30 years old, the clinical stage 2 patients were 31-40 years old, the clinical stage 3 patients were 31-40 years old, and the clinical stage 4 patients were 21-30 years old. The results of the study also revealed that most of the patients in stages 1–4 had a senior high school education, worked as private employees, and lived in urban areas